POTENTIALLY MALIGNANT LESIONS IN THE ORAL CAVITY: A RETROSPECTIVE ANALYSIS - Bianca-Andreea Onofrei; Cristina Popa; Ana Maria Sciuca; Mihaela Paula Toader; Oana Mihaela Condurache Hrițcu; Elena-Raluca Baciu; Delia Gabriela Ciobanu-Apostol; Victor-Vlad Costan (Romanian Society of Oral Rehabilitation, 2024)
The study aimed to present the characteristics of the three most prevalent oral potentially malignant disorders, leukoplakia, oral lichen planus (OLP), and actinic cheilitis, using data from 62 patients collected at the "Sfântul Spiridon" Emergency Clinical Hospital in Iași, Romania, between January 2015 and January 2023. The results revealed a higher prevalence of these lesions among older adults, particularly those over 50 years old, and a significant gender disparity in the incidence of actinic cheilitis, which was more common in males (68%). Leukoplakia was frequently observed on the tongue and lower lip, whereas OLP commonly affected the buccal mucosa. Actinic cheilitis was primarily noted on the lower lip, attributed to chronic sun exposure. The study highlighted the importance of early detection and regular monitoring of these conditions to prevent malignant transformation.